The Effect of Gum Arabic Addition to Physicochemical and Sensory Properties of Pineapple (Ananas comosus L. Merr.) and Carrot (Daucus carota) Fruit Leather - Prasetyowati, Denanda Andini; Widowati, Esti; Nursiwi, Asri (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
The aimed of this research were to determine the effect of gum arabic addition (0.3, 0.6, and 0.9%) to the physicochemical and sensory properties of pineapple and carrot fruit leather and which concentration can be a recommendation in pineapple and carrot fruit leather. This study used Completely Randomized Design (CRD) with one factor of concentration variation of gum arabic. The results analysis of physicochemical pineapple and carrot fruit leather showed that gum arab addition give significant effect on tensile strength, moisture content, and dietery fiber content, but the addition of gum arabic did not significantly affect on ash content and aw. From the sensory properties, pineapple and carrot fruit leather with gum arabic addition affect the color and texture but didnât give significant effect on the aroma, flavor and overall. Based on physicochemical and sensory properties the recommended concentration is 0.6% gum arabic in pineapple and carrot fruit leather.Keywords: fruit leather, pineapple and carrot fruit leather, gum arabic